Peran Rekonsiliasi Keuangan Dalam Meningkatkan Akurasi Laporan Keuangan Bulanan dan Tahunan Pada CV X - Mahmud, Amir; Fitriani, Nurul (International Journal Administration, Business & Organization, 2025)
This research aims to analyze the role of financial reconciliation in improving the accuracy of monthly and annual financial statements at CV X, a machinery distribution company that does not have an internal accounting staff and relies entirely on a Public Accounting Service Office (Kantor Jasa Akuntan or KJA) for its financial reporting process. The approach used in this study is descriptive qualitative, with data collection techniques carried out through interviews, direct observations, and documentation review. The research findings show that the implementation of financial reconciliation, which includes bank reconciliation, accounts receivable and payable reconciliation, inventory reconciliation, and tax reconciliation, significantly improves the reliability of CV X’s financial statements. Before the application of reconciliation procedures, the company’s financial statements were inaccurate, unsystematic, and failed to reflect the actual financial condition. After the periodic implementation of reconciliation, there was a notable increase in transparency, accuracy of recording, and ease of tax reporting processes. Although the process faced challenges such as delays in the submission of data and discrepancies in transaction names, reconciliation proved to be effective in enhancing the company’s financial reporting system. This research recommends the development of a digital reconciliation system and the placement of an internal accounting staff to further strengthen the effectiveness and sustainability of financial management.